Managing recurrent traumatic gingival ulceration secondary to aberrant frenal attachment with modified kazanjian vestibuloplasty: a case report - Mohd Noh, Nur Zety; Salehuddin, Nurul Qamar; Ariffin, Farha (University of Malaya, 2024)
The current study described tooth 45 buccal high frenum attachment of a 56-year-old male patient associated with shallow vestibule adjacent to the edentulous ridge of missing tooth 46 management. The patient reported recurring traumatic ulcers on teeth 44 and 45 buccal gingiva due to frequent toothbrush slippage. The patient also requested an implant for missing tooth 46. A modified Kazanjian vestibuloplasty was performed before replacing the missing tooth. Subsequently, the patient was reviewed at one and two weeks, one month, and monthly for up to six months. The patient did not report traumatic ulcer development within the surgery site and improved plaque control. Consequently, performing mucogingival surgery in cases of inadequate keratinised tissue width, decreased vestibular depth, and high muscle pull is recommended. The procedure facilitates plaque control, reduces or halts gingival recession, and enhances comfort during tooth brushing